Checks and balances, private information, and the credibility of monetary commitments - Keefer, Philip (Policy research working paper, 2001)
In economically volatile conditions in which it is more difficult for the public to distinguish inflation deliberately generated by government from inflation created by unanticipated economic shocks, the anti-inflationary effect of central bank independence will be unchanged but the effectiveness of exchange rate pegs will be significantly improved. Keefer and Stasavage develop and test several new hypotheses about the anti-inflationary effect of central bank independence and exchange rate pegs in the context of different institutions and different degrees of citizen information about government policies